Henri de Lubac's wending naar de kerk - Mulder, Sjoerd (NTT, 2019)
In the last thirty years, theologians such as Milbank and Hauerwas have allowed ecclesiology to play a fundamental role in theology. This move is grounded in their conviction that the meaning of Christianity consists primarily not in its theory and doctrine but in its lived form, which is the church. Interestingly, this contemporary 'turn to the church' in many ways resembles an earlier revival of ecclesiology in the beginning of the twentieth century in Roman Catholic theology. In this paper, I will focus on the work of Henri de Lubac, and demonstrate how the particular way in which he develops his idea of the church might offer valuable insights for contemporary theology. First, I sketch how his particular understanding of the church as the social and historical embodiment of God's gracious action immediately implied an embrace of the social and historical world. Second, I argue that notwithstanding all his emphasis on the church, his particular understanding of the church as springing from the Eucharist means that the church is never idolized but always points beyond itself to God. I conclude by relating these insights to the contemporary turn to the church.